International Child Abduction - Commentary on the Case C-35/23 of the Court of Justice of the European Union - Sousa Gonçalves, Anabela Susana de (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Council Regulation (EC) No 2201/2003 of 27 November 2003 concerning jurisdiction and the recognition and enforcement of judgments in matrimonial matters and the matters of parental responsibility (Brussels II bis) contains the legal framework applicable to international child abduction in the European Union and complements the 1980 Hague Convention on the Civil Aspects of International Child Abduction. It is the application of the Brussels II bis Regulation to a situation of international child abduction that is the issue of the decision of the Court of Justice of the European Union (C-35/23) that is commented on, in particular, doubts in the interpretation of the rule of stability of the jurisdiction of the courts of the habitual residence of the child before the abduction, in the duties of notification and information between the courts of the States involved and in the execution of the return decision.